Intraprofessional conflicts of doctors and nurses: reflection on power in Michel Foucault (Research, Society and Development, 2020)
Objective:  reflecting on relations of power as the cause of intraprofessional conflicts among doctors and nurses inside a hospital, regarding Michel Foucault as theoretical reference. Method: reflective theoretical study, anchored in the following items: 1) Michel Foucault, addressing power, knowledge and domain need; 2) intraprofessional relations, with emphasis on power and competence  in medicine and nursing; 3) power relations in a hospital  and the health system user as the focus. Result:  power and knowledge dynamics and the search for hierarchy by medical and nursing professionals in the hospital  within their respective field of study  might have negative repercussions on the outcome of health care. Conclusion: The understanding of power relations  according to Michel Foucault, who devoted much to the study of the hospital as an institution, might reveal intraprofessional conflicts, impacting on the quality of medical and nursing care to the  client of a hospital.